Entrepreneurial opportunities for Malaysian women in ageing care industry / Shaista Noor and Filzah Md. Isa - Noor, Shaista; Md. Isa, Filzah (Research Management Centre (RMC), 2020)
Malaysia is a developing country and a drastic increase in the elderly population is recorded from the year 2005, ageing population age 60 and above recorded as 7 %, which is predicted to be doubled to 14 % until the year 2028. Thus, the ageing care industry in Malaysia needs to grow for healthy ageing. The growth of the ageing care industry will help the government to control the issues, especially in elderly care service and residency. Malaysia is still young in elderly care as compared to older countries. There are 365 registered ageing care centres, and women run very few of them. However, women personality attributes such as soft nature, politeness, care, patience fit to the requirement of the ageing care industry. Among Malaysian women, entrepreneurship is on the rise due to governmental support, whereas; women entrepreneurship in the service industry is limited. However, women entry in the ageing care industry will open new avenues to cater to the demand of the ageing population and help to control the issues of the older population. The service industry also carries immense potential for women entrepreneurship. This study is conducted to understand the entrepreneurial opportunities for women in the ageing care industry. The study adopts the qualitative research strategy and focus group conducted with ten women entrepreneurs in the ageing care industry and five experts. The results highlight that initiative should take for the promotion and encouragement of women entry in the ageing care industry. The study recommends the validation and promotion of Malaysian women entrepreneurial activities in the ageing care industry.